Assessment of the implications of the Bolsa Família Programme for the Decent Work Agenda - Ana Flavia Machado; Gustavo Geaquinto Fontes; Mariangela Furlan Antigo; Roberto Henrique Sieczkowski Gonzalez; Fábio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2011)
[Introduction ...] The report is divided into six sections, in addition to the present introduction. Section 1 briefly describes the evolution of social protection and of the social security system in Brazil, and the role of the PBF in this system. Section 2 presents the major features of the PBF in general terms. Sections 3 and 4 then review the main studies that have been carried out of the impact of the PBF on the supply of adult and child labour, respectively. Section 3 deals, firstly, with the evolution of the Brazilian labour market in the 1990s and the first decade of this century. A description is then provided, for 2004 and 2006, of the differences in labour market indicators for the heads of both PBF beneficiary and non-beneficiary households, using the PNAD supplement database, which allows a much more robust identification of households with PBF beneficiaries. Section 3 also contains an evaluation of the labour market performance of PBF beneficiaries for the two years using pseudo-cohorts. The decent work approach permeates the present analysis, taking into consideration the limited data available. The study takes into account the employment rate, the degree of formalization of labour relations and the proportion of employed persons in the various income groups, in addition to analysing the prevalence of child labour. The section also includes a description of regional disparities in Brazil in terms of poverty indicators, PBF coverage and labour market indicators. Section 4 examines work by children and adolescents in PBF beneficiary and non-beneficiary households. Complementary programmes for the expansion of employment and earnings opportunities of PBF beneficiaries are reviewed in section 5. Finally, the sixth section contains some concluding remarks.
Keywords: 330